2021
DOI: 10.1038/s41598-021-81836-x
|View full text |Cite
|
Sign up to set email alerts
|

Replication of HLA class II locus association with susceptibility to podoconiosis in three Ethiopian ethnic groups

Abstract: Podoconiosis, a debilitating lymphoedema of the leg, results from barefoot exposure to volcanic clay soil in genetically susceptible individuals. A previous genome-wide association study (GWAS) conducted in the Wolaita ethnic group from Ethiopia showed association between single nucleotide polymorphisms (SNPs) in the HLA class II region and podoconiosis. We aimed to conduct a second GWAS in a new sample (N = 1892) collected from the Wolaita and two other Ethiopian populations, the Amhara and the Oromo, also af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…This may indicate the role of genetic background in the development of podoconiosis [ 3 ]. There are studies which indicated relationship between some HLA Class II variants and occurrence of podoconiosis [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate the role of genetic background in the development of podoconiosis [ 3 ]. There are studies which indicated relationship between some HLA Class II variants and occurrence of podoconiosis [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of HLA-DQB1 in this study is of interest due to the documented association between this gene (as well as HLA-DRB1 ) and podoconiosis 9 , 10 . Variation in the HLA-DQB1 gene and its upregulation have been linked with susceptibility to different solid organ and tissue fibrosis 45 , 46 .…”
Section: Discussionmentioning
confidence: 85%
“…Podoconiosis is a noncommunicable disease caused by exposure to an environmental factor on the background of genetic susceptibility associated with variation in HLA-DR and HLA-DQ genotypes 9 , 10 . Little is known about the environmental trigger or the pathogenic immune response it induces in podoconiosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The last decade has seen a significant increase in studies of Podoconiosis. Improvements are occurring in the understanding of its medical and public health aspects, such as prevention and management, genetic factors, and even community understanding (Alcantara et al, 2020 ; Davey et al, 2007 ; Deribe et al, 2018 ; Florence & Fuller, 2017 ; Gebresilase et al, 2021 ; Molla et al, 2012 ; Tora et al, 2016 ; van‘t Noordende et al, 2020 ). However, research into the soils has not received the same attention, though recent years suggest growing interest (Cooper et al, 2019 ; Gislam et al, 2020 ; Le Blond et al, 2015 ; Molla et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%